A reforma do papado: um caminho possível a partir da recontextualização da Constituição Dogmática Pastor Aeternus e dos anseios dos papas após o Concílio Vaticano II - Dias, Tiago Cosmo da Silva (2022)
The present research intends to reflect on the way and from which parameters a reform could be carried out in the exercise of the papal ministry. This analysis, in turn, is only possible at this moment because, in 2013, Cardinal Jorge Mario Bergoglio was elected bishop of Rome and, from then on, he began an unprecedented movement of reform in various areas of ecclesial life. The point, however, is that, as far as the papacy is concerned, in 1870 the First Vatican Ecumenical Council defined, as divinely revealed dogmas of faith, that the pope is infallible in matters of faith and morals, when he speaks ex cathedra, and which has a primacy of jurisdiction over the whole Church. In this scenario, calls for reform, no matter how consistent they may be, need to be reflected taking these truths of faith into account and without hurting them, in a sense, since in the Church dogmas are the definitive word. Despite this, a look at history helps to verify that these prerogatives were not always clear, in the same way that there is not necessarily a biblical basis to justify them from the apostle Peter. Therefore, the proposal for a reform in the papacy needs to go through a look at history, a serious review of papal titles, the humanization of the pope, the emphasis on the experience of collegiality and, of course, the practice of the preferential option for the poor, realities that, in the pontificate of Pope Francis, are more than alive in their words and gestures